Dzehkabtún: The history of a habitational complex from the Late Classic to the Terminal Classic - Paap, Iken (Restauro Compás y Canto S.A., 2021)
This text describes and analyzes the history of an architectural group of the Classic Maya in the central peninsula of Yucatan, Edo. de Campeche, Mpo. de Hopelchén. The excavation of a habitational complex in Dzehkabtún and the analysis of the associated material allow us to reconstruct part of the development of the site from the Late Classic to the Terminal Classic. The analysis of osteological materials from several burials stratigraphically linked to the construction phases of the central building of this group revealed a high level physical stress, which probably worsened towards the Late Classic when acts of violence such as the intentional destruction of the vaulted buildings were recorded.